The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1982-0224-2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

Age validation and contrasted growth performances of Pseudoplatystoma punctifer (Siluriformes: Pimelodidae) in two river systems of the Western Amazon

Maricell Armas,
Hernán Ortega,
Aurea García-Vasquez
et al.

Abstract: The doncella Pseudoplatystoma punctifer is an economically and ecologically important catfish in the Amazon basin. However, little is known about its age, growth and population dynamics parameters. This study aims to validate the formation of growth marks in vertebrae of individuals collected from two rivers systems of the Peruvian Amazon (Amazon-Marañón-Ucayali and Putumayo) and compare growth parameters using the von Bertalanffy growth function between sexes and systems. A total of 372 individuals from the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…As noted above, these catfishes are large-bodied compared to other Neotropical species and can grow up to about 130 cm in total length and 100 kg in weight, depending on the species [56]. They can grow to 40 cm in their first year of life [14]. Females grow larger and faster than males.…”
Section: Growthmentioning
confidence: 94%
See 4 more Smart Citations
“…As noted above, these catfishes are large-bodied compared to other Neotropical species and can grow up to about 130 cm in total length and 100 kg in weight, depending on the species [56]. They can grow to 40 cm in their first year of life [14]. Females grow larger and faster than males.…”
Section: Growthmentioning
confidence: 94%
“…Most studies on the growth of Pseudoplatystoma found a similar pattern of growth rings in calcified structures such as otoliths and vertebrae, with opaque ring formation in the hard parts of Pseudoplatystoma, indicating fast growth occurring during the dry season [14,31,50,58,60]. Several studies showed that one opaque ring is formed annually during the dry season and the beginning of the rainy season for P. punctifer, P. tigrinum, and P. mataense in the Peruvian Amazon, Orinoco, and Mamore basins [14,31,57], probably because the dry season is when prey capture is more difficult due to competition with larger catfishes and dolphins and the beginning of the reproductive stage [14,31,33]. However, studies on central and eastern Amazon tributaries are necessary to determine whether the pattern of one ring per annual cycle is consistent for P. fasciatum and P. tigrinum.…”
Section: Growthmentioning
confidence: 96%
See 3 more Smart Citations